Social Structure of Lions (Panthera leo) Is Affected by Management in Pendjari Biosphere Reserve, Benin - SOGBOHOSSOU, ETOTEPE A.; BAUER, Hans; LOVERIDGE, Andrew; FUNSTON, Paul J.; DE SNOO, Geert R.; Sinsin, Franck; DE IONGH, Hans H. (My University, 2014)
Lion populations have undergone a severe decline in West Africa. As baseline for conservation management, we assessed the group structure of lions in the Pendjari Biosphere Reserve in Benin. This reserve, composed of one National Park and two Hunting Zones, is part of the WAP transboundary complex of protected areas. Overall mean group size was 2.661.7 individuals (n=296), it was significantly higher in the National Park (2.761.7, n=168) than in the Hunting Zones (2.261.5, n=128). Overall adult sex ratio was even, but significantly biased towards females (0.67) in the National Park and towards males (1.67) in the Hunting Zones. Our results suggest that the Pendjari lion population is affected by perturbations, such as trophy hunting.
Keywords: Large carnivores; group sizes; sex structure; hunting; West Africa